Creating a Sharing Culture: A Social Capital-informed Systematic Review of Leadership Support and Organisational Culture Interventions for Knowledge Sharing in Public Higher Education Institutions (2010-2024) - Matsobane Daniel Kekana; Masego Tumelo Maungwa (European Conference on Knowledge Management, 2026)
Knowledge sharing is repeatedly identified as critical to institutional learning and performance in public higher education institutions (HEIs), yet the evidence base remains fragmented regarding which leadership behaviours and organisational culture interventions actually change sharing practices in academic settings. Existing studies often emphasise barriers to knowledge sharing, with less synthesis of solution-oriented interventions, particularly within the bureaucratic and resource-constrained environments of publicly funded HEIs and vocational institutions. Applying the social capital theory to this systematic review adds a theoretical layer that deepens the analysis of how organisational culture and leadership support foster knowledge sharing. This study reports a systematic review (2010–2024) that synthesises empirical evidence on leadership and organisational culture interventions implemented to foster knowledge sharing among academics. Using a PRISMA-guided protocol, we will search major scholarly databases for peer-reviewed journal articles, case studies, and relevant book chapters, apply transparent inclusion/exclusion criteria, and manage screening in Covidence. The included studies will be analysed using qualitative content analysis to identify intervention types, leadership approaches, implementation conditions, and reported outcomes related to knowledge-sharing behaviours and culture change. The review will contribute (1) an evidence-based taxonomy of leadership and institutional interventions for knowledge sharing in public HEIs, (2) an assessment of reported effectiveness and common outcome measures, and (3) an integrative framework linking contextual constraints, social–psychological mechanisms (e.g., trust, psychological safety, incentives), and intervention outcomes. The findings aim to support both KM scholarship and institutional leaders seeking actionable strategies to build sustainable knowledge-sharing cultures in public higher education.